Appropriation and Subversion: Precommunist Literacy, Communist Party Saturation, and Postcommunist Democratic Outcomes. (23rd February 2016) - Lankina, Tomila V.; Libman, Alexander; Obydenkova, Anastassia
Abstract : Twenty-five years after the collapse of communism in Europe, few scholars disagree that the past continues to shape the democratic trajectories of postcommunist states. Precommunist education has featured prominently in this literature's bundle of "good" legacies because it ostensibly helped foster resistance to communism. The authors propose a differentcausal mechanism—appropriation and subversion—that challenges the linearity of the above assumptions by analyzing the effects of precommunist literacy on patterns of Communist Party recruitment in Russia's regions. Rather than regarding precommunist education as a source of latent resistance to communism, the authorshighlight the Leninist regime's successful appropriation of the more literate strata of the precommunist orders, in the process subverting the past democratic edge of the hitherto comparatively more developed areas. The linear regression analysis of author—assembled statistics from the first Russian imperial census of 1897 supports prior research: precommunist literacy has a strong positive association with postcommunist democratic outcomes. Nevertheless, in pursuing causal mediation analysis, the authors find, in addition, that the above effect is mediated by Communist Party saturation in Russia's regions. Party functionaries were likely to be drawn from areas that had been comparatively more literate in tsarist times, andparty saturation in turn had a dampening effect on the otherwise positive effects of precommunist education on postcommunist democracy.